Concept of Discretion Reviewed from the Humanistic Side Based on Law of the Republic of Indonesia Number 30 of 2014 Concerning Government Administration - Soehartono, Arsyad Aldyan (International Journal of Advanced Science and Technology, 2020)
Law of the Republic of Indonesia Number 30 the Year 2014 Regarding Government Administration accommodates this contradictory situation by stating the regulation on discretion in Articles 22 to 33. The existence of this regulation on discretion makes the government free to take action on an event that occurs but still has a legal basis. Discretion is the freedom to think, weigh, and assess what is in each individual. This freedom will later lead the individual to a decision and action in which the existence of the decision and action is considered to produce ideal conditions. Associated with the context from government administration, discretion must also be understood as a process, not as an outcome. The purpose of the use of discretion, as referred to in Article 22 paragraph (2) of the Government Administration Act, actually has a humanist goal, namely to prioritize the achievement of the needs of the government community itself as the user of the discretion.